Allotment keeping in Ljubljana - Smrekar, Ales (IGiPZ PAN, 2009)
This article introduces the issue of the planning of allotment gardening in the case of Ljubljana, Slovenia, as a self-supplying activity by which fresh vegetables are cultivated. Allotment gardening is an activity that involves just a small percentage of Ljubljana’s population, those enthusiasts seeing this activity as more of a recreation and relaxation than a way of earning money. The city authorities are already anticipating that allotments will be eliminated from locations deemed unsuitable, holders then being offered alternatives in more appropriate locations. The appropriateness of these planned locations for allotments was evaluated in respect of whether key exclusion and attractiveness measures were complied with. We also determined the partial suitability of selected locations.
24 cm
Keywords: allotment gardening and keeping; allotment gardens; leisure actvity; protection of the environment; spatial planning; Ljubljana; Slovenia